(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Investments in securities at the current stage of economic development are the most profitable ways to invest money, so this article presents an assessment of financial investments of commercial banks for 2018 and 2020. A comparison of the 10 largest commercial banks in terms of financial investments was made, and conclusions were drawn about the success of their investment activities.